Cost of Agricultural Credit in Punjab: Institutional Vis-À-Vis Non-Institutional Sources. - Arjinder Kaur and Sidhu, R.S (2013)
The cost of credit is an important factor having widespread ramifications for the agriculture sector. The present study is based on primary data collected from 320 households across three agro climatic zones of Punjab state to bring out various aspects pertaining to agricultural credit. For the state, average transaction cost of borrowing is calculated to be Rs.861 per farm while availing credit from institutional sources of finance with highest components like bribe paid at various stages of the loan case, followed by food expenses incurred during various trips to these agencies and legal charges for the loan case, etc. With the increase in the size of operational holdings the transaction cost is increasing. But, when compared with non-institutional sources of finance, the total cost borne by the farmer is still significantly less despite the higher transaction cost. A farmer had to undertake 5.49 trips to the institutional source and on an average 18.15 days are taken to complete the loan procedure while borrowing from institutional sources. On the other hand, the number of trips was found to be 1.17 and average time to avail loan from non-institutional sources was 3.59 days. So, the ease, timeliness, convenience, informal atmosphere attached to informal source of finance explains the reason for their non-elimination from agricultural credit scenario.